Enhanced Photovoltaic Performance of Benzothiadiazole‐Based Polymers by Controlling their Backbone Planarity for Organic Solar Cells. Issue 22 (11th October 2022) - Tamilavan, Vellaiappillai; Kim, Danbi; Yang, Hyun‐Seock; Shin, Insoo; Kim, Junghwan; Lee, Bo Ram; Park, Sung Heum
Abstract: Here, a new synthetic strategy for converting low‐energy benzo[c][1, 2, 5]thiadiazole (BT)‐based polymers into efficient polymeric donors for non‐fullerene acceptor‐based organic solar cells (NFA–OSCs) is demonstrated. A highly planar 5, 6‐difluoro‐benzo[c][1, 2, 5]thiadiazole (ffBT)‐based alternating polymer, P1, comprising of electron‐rich 4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b']dithiophene (BDTT) and strong electron‐deficient 5, 6‐difluoro‐4, 7‐bis(4‐octylthiophen‐2‐yl)benzo[c][1, 2, 5]thiadiazole (DTffBT) units is prepared. Additionally, two ternary polymers, P2 and P3, are preparedby replacing 25% and 50% of the DTffBT unit on the P1 backbone with a weak electron‐deficient 2, 5‐dioctyl‐4, 6‐di(thiophen‐2‐yl)pyrrolo[3, 4‐c]pyrrole‐1, 3(2H, 5H)‐dione (DTPPD) unit, which has a twisted but well‐controlled wavy backbone. The properties of the resulting polymers, P1–P3, are investigated to understand the effects of changing the planarity and curvature of the backbone of the BT‐based polymers. Notably, increasing the concentration of the DTPPD unit on P1 results in ablue‐shift in absorption band and relatively deep energy levels. Further, the π–π stacking of the polymers is decreased by increasing the amount of DTPPD units on P1. The NFA–OSCs fabricated using P1–P3 as the electron donor afford maximum power conversion efficiencies (PCE) of 2.46%, 4.52%, and 7.54%, respectively. Overall, the photovoltaic performance of the BT‐based polymers is significantly improved by lowering their planarity and/or changing their backbone curvature. Abstract : A non‐planar unit, namely DTPPD, is inserted in planar structured benzothiadiazole‐based polymer (P1). The inclusion of DTPPD units resulted in twisted backbone, blue shift absorption, and deeper energy levels for the resulting polymers (P2 and P3). P2 and P3 displayed higher PCE than P1 when they blended with electron acceptors due to their good complementary absorption and energy levels.